Pengelolaan Dana Hibah pada Masjid Fadhlul A’zim di Kota Bengkulu (Perspektif Akuntansi Syariah) - Anela Nistiani; Desi Isnaini; Yuninda Een Friyanti (Universitas Muhammadiyah Surabaya, 2026)
This study aims to analyze the management of grant funds at Fadhlul A’zim Mosque in Bengkulu City from the perspective of Islamic accounting. The research focuses on the processes of planning, receiving, utilizing, and reporting grant funds, as well as the implementation of Islamic values such as trustworthiness, honesty, transparency, and accountability in mosque financial management. This study employed a qualitative approach using a case study method. Data were collected through observation, in-depth interviews, and documentation involving mosque administrators, congregants, and related parties. Data analysis was conducted using the Miles and Huberman interactive model consisting of data reduction, data presentation, and conclusion drawing. The results indicate that the management of grant funds at Fadhlul A’zim Mosque has been carried out systematically through deliberation, proposal preparation, phased fund disbursement, allocation of funds for mosque development, and preparation of accountability reports. Islamic values have been implemented through transparency in financial information and the appropriate use of funds according to predetermined objectives. However, the financial recording and reporting system is still relatively simple and has not fully complied with PSAK No. 45 concerning nonprofit financial reporting standards. Therefore, improvements in accounting systems and financial reporting practices are needed to achieve more professional, transparent, and Sharia-compliant grant fund management.